Comparing and evaluating the efficacy of methotrexate and actinomycin D as first-line single chemotherapy agents in low risk gestational trophoblastic disease - Lee, Young-Jae; Park, Jeong-Yeol; Kim, Dae-Yeon; Suh, Dae-Shik; Kim, Jong-Hyeok; Kim, Yong-Man; Kim, Young-Tak; Nam, Joo-Hyun (Journal of gynecologic oncology, 2017)
The aim of this study was to compare responses to single-agent chemotherapies and evaluate the predictive factors of resistance in low risk (LR) gestational trophoblastic disease (GTD). The chemotherapy agents included methotrexate (MTX) and actinomycin D (ACT-D). We conducted a retrospective study of 126 patients with GTD who were treated between 2000 and 2013. A total of 71 patients with LR GTD were treated with MTX (8-day regimen or weekly regimen, n=53) or ACT-D (bi-weekly pulsed regimen or 5-day regimen, n=18). The successful treatment group and the failed treatment group were compared and analyzed to identify prognostic factors. The complete response rates were 83.3% for ACT-D and 62.2% for MTX, with no statistically significant difference. There was no severe adverse effect reported for either group. Longer interval durations from the index pregnancy (>2 months, p=0.040) and larger tumor size (>3 cm, p=0.020) were more common in non-responders than in responders; these results were statistically significant. Based on our results, ACT-D may be a better option than MTX as a first-line single chemotherapy agent for LR GTD. The bi-weekly pulsed ACT-D regimen had minimal, or at least the same, toxicities compared with MTX. However, due to the lack of strong supporting evidence, it cannot be conclusively stated that this is the best single agent for first-line chemotherapy in LR GTD patients. Further larger controlled trials will be necessary to establish the best guidelines for GTD treatment.